70-487 developing Microsoft Azure and web services. - Wayani, Rafiq; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"This course will help students prepare for Developing Microsoft Azure and Web Services certification. The 70-487 Certification is intended for developers with 3 to 5 years experience in web services development and a minimum of one year in Web API and Azure Solutions experience."--Resource description page.
Presenter, Rafiq Wayani.
Title from resource description page (Safari, viewed November 10, 2017).
Presenter's name from title screen.
Keywords: Windows Azure -- Examinations -- Study guides; Cloud computing -- Examinations -- Study guides; Application program interfaces (Computer software) -- Examinations -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books